Between play and the screen: the repercussions on children's emotional development (Research, Society and Development, 2020)
This article aims to reflect on the possible repercussions on children's emotional development when playing occurs permeated by technological devices. To this end, a literature review was performed based on classical and contemporary psychoanalytic authors. Although the literature affirms the act of playing as indispensable for the understanding of the psychic constitution and child emotional development, it proves to be being replaced by technological devices in contemporary times. However, this does not happen without consequences for child development, reflecting on aspects of language, symbolization, relationships, play, make-believe and creativity. Still, the implications on emotional development are associated with the way these devices are used with regard to parental frequency and mediation. The act of playing only through devices does not encompass the affective investments that are fundamental to the child's subjectification in a relationship. Given this and realizing the lack of information on the part of the main caregivers, it becomes relevant to share the knowledge acquired to them so that they can account for the care of the child together with society.